2018
DOI: 10.3389/fnint.2018.00016
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Resting State Network Abnormality in Adults Who Stutter

Abstract: Neural network-based investigations of stuttering have begun to provide a possible integrative account for the large number of brain-based anomalies associated with stuttering. Here we used resting-state EEG to investigate functional brain networks in adults who stutter (AWS). Participants were 19 AWS and 52 age-, and gender-matched normally fluent speakers. EEGs were recorded and connectivity matrices were generated by LORETA in the theta (4–8 Hz), alpha (8–12 Hz), beta1 (12–20 Hz), and beta2 (20–30 Hz) bands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 100 publications
(167 reference statements)
1
24
0
Order By: Relevance
“…1). To date, many studies have been carried out using MST to reconstruct the global neural networks in such clinical conditions as, for example, epilepsy 29,30 , stuttering 31 , Alzheimer’s disease 32 and in brain maturation research 33 . These studies confirmed the usefulness of the MST algorithms to identify network irregularities in the mentioned populations.…”
Section: Introductionmentioning
confidence: 99%
“…1). To date, many studies have been carried out using MST to reconstruct the global neural networks in such clinical conditions as, for example, epilepsy 29,30 , stuttering 31 , Alzheimer’s disease 32 and in brain maturation research 33 . These studies confirmed the usefulness of the MST algorithms to identify network irregularities in the mentioned populations.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of the EEG part of the study is the use of a relatively small number of electrodes, however, EEG assessments in a real clinical setting are usually conducted with 19 or 21 scalp electrodes. Although the number of EEG electrodes is related to the precision of source estimation, several studies indicate that a reliable LORETA/eLORETA estimation can be achieved with just 19 channels (91)(92)(93)(94)(95)(96). Nevertheless, eLORETA accuracy still depends to an extent on the EEG montage density and the relatively small number of electrodes that we were limited to suggest some caution in interpreting our findings.…”
Section: Limitationsmentioning
confidence: 81%
“…Although high-density EEG studies with more than 64 recording channels can display a highly spatial resolution of brain function and the number of electrodes or nodes can improve the GTA analysis, several recent studies with limited recording channels indicate that reliable results can also be obtained using standard 10/20 system with 19 EEG channels 12,13,[60][61][62][63] . In order to compute a functional brain network, we used coherence as a simple and well-studied EEG connectivity measure 4,12,14,[64][65][66][67] .…”
Section: -3 Eeg Connectivity and Adjacency Matrixmentioning
confidence: 99%
“…Mathematically, the leaf fraction is equal to the number of nodes with a degree of value equal to '1' (N (k=1) ) divided by N-1, where N represents the total number of nodes in a tree 51 . When the tree has a central node connected to all other nodes, the value of the leaf fraction is maximal; on the other hand, the leaf fraction is at a minimum for a tree with a line shape where one node is connected uniquely to another node in the network 13 . In terms of integration of a network, trees with a network in the shape of a line that have low leaf fraction value are deemed to be less integrated than graphs with a flower shape and high leaf fraction value 56 .…”
Section: -4-2 Minimum Spanning Tree (Mst) Analysismentioning
confidence: 99%
See 1 more Smart Citation